2020
DOI: 10.3174/ajnr.a6560
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Effects on Cortical Thickness in Children and Adults with Attention-Deficit/Hyperactivity Disorder: A Randomized Clinical Trial

Abstract: BACKGROUND AND PURPOSE: Although methylphenidate is frequently used to treat children with attention-deficit/hyperactivity disorder, it is currently unknown how methylphenidate affects brain development. In a randomized controlled trial, we investigated whether the cortical effects of methylphenidate are modulated by age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Despite these limitations, the following two advantages enhance the reliability of the results. Previous studies have outlined that stimulants can change the brain structure and function of patients with ADHD ( An et al, 2013 ; Querne et al, 2017 ; Walhovd et al, 2020 ) and the dose of the stimulant correlates with the size of the amygdala ( Becker et al, 2015 ). The participants selected for this study were not on any stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the following two advantages enhance the reliability of the results. Previous studies have outlined that stimulants can change the brain structure and function of patients with ADHD ( An et al, 2013 ; Querne et al, 2017 ; Walhovd et al, 2020 ) and the dose of the stimulant correlates with the size of the amygdala ( Becker et al, 2015 ). The participants selected for this study were not on any stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…A report from the same trial described increasing cortical thickness in medicated children within right medial frontal cortex, which contrasted with the cortical thinning that was observed in the placebo group. No significant results were found for the adult groups, and structural brain changes were not associated with clinical improvement [70].…”
Section: Structural and Functional Neuroimagingmentioning
confidence: 82%
“…Both acute and longer-term treatment effects on brain patterns have been documented using structural and functional magnetic resonance imaging in ADHD samples (Table 4 ). Changes in structural neuroimaging markers following treatment with MPH have been studied as part of a 16-week double-blind, randomized, placebo-controlled trial of boys and young men with ADHD [ 69 , 70 ]. One report from this trial showed wide-spread time-by-medication-by-age interaction effects in left hemisphere white matter, which were driven by increases in fractional anisotropy among medicated children [ 69 ].…”
Section: Monitoring and Response/pharmacodynamic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of MPH are usually attributed to its ability to block the reuptake of dopamine, noradrenaline, and (in low affinity) serotonin to potentiate the effects of monoamines in the synaptic cleft ( Quintero et al, 2022 ). Nevertheless, accumulating evidence suggests that the ability of MPH to stimulate cortical maturation [responsible for its long-term effects ( Shaw et al, 2009 ; Walhovd et al, 2020 )] may be mediated by a separate mechanism not related to the inhibition of monoamine transporters ( Bartl et al, 2010 , 2013b , 2017 ; Grünblatt et al, 2018 ; Yde Ohki et al, 2020 ). It has been reported that MPH can inhibit proliferation and enhance neuronal differentiation both in vitro ( Bartl et al, 2013b ; Grünblatt et al, 2018 ) and in vivo ( Lee et al, 2012 ; Oakes et al, 2019 ) via an unknown molecular mechanism.…”
Section: Methylphenidate In Attention-deficit Hyperactivity Disorder ...mentioning
confidence: 99%